Diacetyl (Butanedione) – Method for the determination of diacetyl in workplace air using gas chromatography‐mass spectrometry (GC‐MS) [Air Monitoring Methods, 2016]. Issue 2 (28th April 2017) - Schuh, C.; Kirchner, M.; Hebisch, R.; Brock, T.H.; Hartwig, A.; ,
Abstract : This analytical method is a validated measurement procedure for the determination of 2, 3‐butanedione (diacetyl) in workplace air in a concentration range of a tenth up to twice the currently valid Occupational Exposure Limit (OEL) or MAK value. Sampling is performed by drawing a defined volume of air through a silica gel tube using a suitable flow‐regulated pump with a volumetric flow rate of 0.33 L/min. For sampling 1 hour or 15 min (checking the short‐term value) can be used. The collected diacetyl is desorbed with acetone containing the internal standard cyclohexanone and then analysed by means of gas chromatography‐mass spectrometry (GC‐MS). Quantitative evaluation is based on a 10‐point calibration using cyclohexanone as internal standard. The limit of quantification for diacetyl is 0.0034 mg/m 3 based on an air sample volume of approx. 20 L or 0.0137 mg/m 3 based on an air sample volume of approx. 5 L (for short‐term value). Joint Publication of the Analytical Subcommittee of the Chemistry Board of Experts of the Expert Committee Raw Materials and Chemical Industry of the German Social Accident Insurance and the Working Group "Air Monitoring Methods" of the Permanent Senate Commission of the DFG for the Investigation of Health Hazards of Chemical Compounds in the Work Area.